Interpretation of a Trust Deed – Harvey v Crawford 2019 (2) SA 153 (SCA) - Ferreira, S; Pretorius, CJ (Obiter, 2020)
Recently, in Harvey v Crawford (2019 (2) SA 153 (SCA)) (Harvey), the Supreme Court of Appeal had to consider whether the adopted grandchildren of a trust donor were beneficiaries in terms of a notarially executed deed of trust. Presently, an adopted child is for all purposes regarded as the child of the adoptive parent, and an adoptive parent is for all purposes regarded as the parent of the adopted child (s 242(3) of the Children’s Act 38 of 2005) (the Children’s Act)). This was also the case in 1953, when the deed of trust in Harvey was executed and when the Children’s Act 31 of 1937 (the 1937 Act) regulated adoption. However, contrary to current legislation, the 1937 Act included a proviso with regard to property that was included in an instrument prior to the date of the adoption order: the instrument was required to display a clear intention that such property would indeed devolve upon an adopted child.Upon interpretation of the deed in question, the court ruled that the adopted children were not entitled to benefit from the capital in the trust. In this regard, the majority opted for a rather restrictive approach, seemingly out of step with recent developments in the interpretation of contracts. The minority decision, on the other hand, came to the opposite conclusion, displaying a more balanced approach to the issue of interpretation. This decision raises some noteworthy issues regarding the interpretation of inter vivos trust deeds with specific reference to adoption. It is submitted that the court erred in its findings; the aim of this case discussion is to analyse the judgment.